Hubungan Perilaku Hidup Bersih dan Sehat dengan Kejadian Diare pada Balita di Kelurahan Mangga Dua Selatan - Azzira Zahwa Yulgian; Dameria Br Saragih; Ernawati (Pustaka Galeri Mandiri, 2026)
Diarrheal disease remains one of the leading causes of death among children under five in Indonesia. One preventive effort against diarrhea is the implementation of Clean and Healthy Living Behavior (PHBS). However, many mothers have not fully applied PHBS in their daily lives. To determine the relationship between Clean and Healthy Living Behavior and the incidence of diarrhea among children under five in Kelurahan Mangga Dua Selatan, Central Jakarta. This study used a descriptive quantitative method with a correlational analytic design and a cross-sectional approach. The population consisted of mothers with children under five, and a total of 92 respondents were selected using simple random sampling. The instruments used were PHBS questionnaires and diarrhea incidence questionnaires. Data were analyzed using the chi-square test. The study found that 51.1% of mothers did not adhere to PHBS, and 88% of children under five experienced diarrhea in the past year. The chi-square test showed a significant relationship between PHBS and diarrhea incidence (p = 0.020 < 0.05), indicating that PHBS influences diarrhea occurrence in toddlers. The lower the mother's adherence to PHBS, the higher the risk of diarrhea in their children